2018
DOI: 10.18203/2349-2902.isj20181572
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of VAC versus conventional dressings in patients with lower limb ulcer

Abstract: Background: Chronic leg ulcers are a significant cause of morbidity in developing countries causing a significant burden on the health care system. The orthodox methods of dressing the wound requires long duration of hospital stay. The recent technique of vacuum assisted closure (VAC) has brought about new horizons in wound management with better outcomes.Methods: A comparative randomized case control study was conducted with a total of 60 patients from November 2015 to December 2017 in patients admitted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Janugade et al showed that most common type of ulcer in VAC (Vaccum Assisted Closure) Group and Conventional dressing was diabetic ulcer (43.3% and 40% respectively) followed by bedsore (26.7% and 33.3% respectively). 8 Priyatham et al showed type of ulcer in VAC and Conventional dressing as diabetic ulcer (33.33 and 35% respectively) followed by bedsore (18.33% and 26.66%), vascular ulcer (36.66% and 23.33%) and traumatic ulcer (11.66% and 15%) respectively which are comparable to our result. 7 This clearly justifies that India is the diabetes capital and with rampant poverty and nutrition with poor glycaemic control diabetic ulcers are common.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Janugade et al showed that most common type of ulcer in VAC (Vaccum Assisted Closure) Group and Conventional dressing was diabetic ulcer (43.3% and 40% respectively) followed by bedsore (26.7% and 33.3% respectively). 8 Priyatham et al showed type of ulcer in VAC and Conventional dressing as diabetic ulcer (33.33 and 35% respectively) followed by bedsore (18.33% and 26.66%), vascular ulcer (36.66% and 23.33%) and traumatic ulcer (11.66% and 15%) respectively which are comparable to our result. 7 This clearly justifies that India is the diabetes capital and with rampant poverty and nutrition with poor glycaemic control diabetic ulcers are common.…”
Section: Discussionsupporting
confidence: 90%
“…The results are comparable with our result. 8 The most common type of ulcer in Group A and Group B was diabetic ulcer (70% and 66.66% respectively) followed by ischemic ulcer (18.33% and 18.33% respectively) followed by venous ulcer (11.66% and 15% respectively). There was no significant difference between the groups as per Chi-Square test (p>0.05).…”
Section: Discussionmentioning
confidence: 87%